PEMANFAATAN GOOGLE FORM DAN KONEKSI KE EXCEL DALAM PENGAJARAN DI SMA MA’ARIF BANDUNG - Abdurrohim, Iim; Rahman, Alkautsar; Yasri; Atmaja, Subhanjaya Angga; Hariman, Irman; Hadikaryana, Oscar; Suprihadi, Deni (JURNAL PENGABDIAN KEPADA MASYARAKAT (JPKM) KEBANGSAAN, 2025)
This community service activity aims to improve the digital competence of teachers in utilizing Google Forms and connecting it to Excel to support the learning process at SMA Ma’arif Bandung. The methods used include theoretical training and hands-on practice, where participants were introduced to Google Form components, how to create evaluation forms, and techniques to integrate them with Excel for data analysis. The results showed that the training successfully improved participants’ understanding and skills in using digital tools for education, although challenges remained during the follow-up mentoring phase. This activity is expected to be an initial step towards digital transformation in the school environment.